Socio-Technical Infrastructure Norms for Fair Use of Artificially Intelligent Education Companions: A Work in Progress (International Conference on Computers in Education, 2022)
Use of artificially intelligent companions in education is widely appealing to learners, educational institutions, and the education technology sector. However, the use of such technology is not inherently fair, with issues such as cost, integration, security, privacy, opportunity, ethics, learning goals influencing their ability to empower and support learners. A framework to support a cross-disciplinary dialogue about the socio-technological infrastructure surrounding companions, to develop fair use implementation, is proposed